Covid-19 management by farmers and policymakers in Burkina Faso, Colombia and France: Lessons for climate action. (May 2021) - Andrieu, N.; Hossard, L.; Graveline, N.; Dugue, P.; Guerra, P.; Chirinda, N.
Abstract: CONTEXT: During crises, adaptation or recovery measures or plans at local or national scales may not necessarily address longer-term or structural problems such as climate change mitigation. OBJECTIVE: This article describes farmers and policymakers' responses to mitigate the adverse effects of Covid-19 on the agricultural sector. We then assess the responses' possible effects on greenhouse gas (GHG) emissions. METHODS: The study is based on surveys conducted with farmers, traders, and extension staff in Burkina Faso, Colombia, and France, and literature. We used the Cool Farm Tool calculator to assess GHG emissions associated with fertilizer production, crop production and produce transportation to international markets for the three main cash crops in the three countries. RESULTS AND CONCLUSIONS: We identified contrasting responses by the agricultural sector mostly driven by changes in the consumption patterns at local or international levels. We also identified contrasting state responses to mitigate Covid-19. These responses at farm and policy scales led to similar trends in decreasing carbon dioxide (CO2 ) emissions across the studied countries. However, none of the studied countries linked Covid-19 response measures to long-term climate change mitigation actions. Therefore, an opportunity to sustain Covid-19 induced short-term decreases in GHG emissions was overlooked. SIGNIFICANCE: Analyzing the impacts that Covid-19 had on agricultural systems and the decision taken by policymakers to handle its direct and indirect effects can help society draw lessons on how to improve climate action. Graphical abstract: Unlabelled Image Highlights: Context/background: Recovery measures to mitigate Covid-19 challenges present an opportunity to address longer-term climate change mitigation challenges, simultaneously. Objective: We evaluate farmer and policy responses to the Covid-19 crisis and estimate resultant greenhouse gas emissions from three cash crop value chains. Results: State and farmers responses to Covid-19 differed between countries and cash crop value chains but resulted in decreases of CO2 emissions. Conclusions: Lack of incentives for climate actions in Covid-19 responses suggests an opportunity to sustain the short-term CO2 emissions decreases was overlooked. Significance: The Covid-19 responses point to a need for better integration and leveraging of future pandemic actions to address other long-term challenges.